Formative Evaluation of Digital Learning Materials - Sri Mertasari, Ni Made; Candiasa, I Made (Universitas Pendidikan Ganesha, 2022)
The use of digital learning materials through e-learning is expected to give students experience to be able to learn themselves in the industrial era 4.0. This study aims to formulate an evaluation method for digital learning materials that is relevant to the development model used. A qualitative approach with an evaluative design through in-depth analysis is applied to student research reports, specifically research on the development of digital learning materials. The formative evaluation method chosen and the reasons for the selection were analyzed and the results were discussed in a focus group discussion. The sample was taken from the results of research by prospective teacher. Expert review was conducted to test the validity of the content and test the design. Content validity test can be done qualitatively or quantitatively by applying Lawshe, Aiken, or Gregory techniques. The design test was carried out with a black-box test. White-box testing is very rarely implemented and is recommended when developing using a programming language. One-to-one and small group tests were conducted using think aloud, cognitive walk through, or heuristics techniques. The results of the analysis found that the formative evaluation methods of teaching materials needed were expert review, one-to-one, small group, and field evaluation. Furthermore, for field tests, inquiry methods can be applied with various techniques, such as learning object review instrument (LORI), user experience questionnaire (UEQ), or system usability scale (SUS).